A rare case of absent left common carotid artery with bovine origin of the left external carotid artery. (8th October 2016) - Goyal, Sumit; Sinha, Ajit Kumar
Abstract : A 22-year-old man had cerebral venous sinus thrombosis and his angiogram incidentally revealed an absent left common carotid artery with bovine origin of the left external carotid artery. There was also an associated low bifurcation of the right common carotid artery and basilar artery fenestration. The absence of a common carotid artery is a very rare angiographic finding, and an association with a bovine origin of the left external carotid artery has not been reported previously in the literature. Here we provide a description of the case along with a review of the literature and embryology.